2017
DOI: 10.3390/mi8100307
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Solvent-Free Formation of Embedded PDMS-Derived Carbon Nanodomains with Tunable Fluorescence Using Selective Laser Ablation with A Low-Power CD Laser

Abstract: We present a study of the application of a single-step and solvent-free laser-based strategy to control the formation of polymer-derived fluorescent carbon nanodomains embedded in poly-dimethylsiloxane (PDMS) microchannels. A low-power, laser-induced microplasma was used to produce a localised combustion of a PDMS surface and confine nanocarbon byproducts within the exposed microregions. Patterns with on-demand geometries were achieved under dry environmental conditions thanks to a low-cost 3-axis CD-DVD platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…8 Graphitic nanocrystals and multi-walled carbon nanotubes have been identified as products of laser-induced combustion and the composition of these products is dependent on laser intensity and other process parameters. 9,10 Our own experiments show that the residue from laser-induced combustion of silicone rubber is indeed electrically conductive. We therefore propose the use of laser scribing as a method to produce electrically conductive patterns on the surface of deposited silicone elastomer during the 3D printing process via chemical conversion of the silicone material.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…8 Graphitic nanocrystals and multi-walled carbon nanotubes have been identified as products of laser-induced combustion and the composition of these products is dependent on laser intensity and other process parameters. 9,10 Our own experiments show that the residue from laser-induced combustion of silicone rubber is indeed electrically conductive. We therefore propose the use of laser scribing as a method to produce electrically conductive patterns on the surface of deposited silicone elastomer during the 3D printing process via chemical conversion of the silicone material.…”
Section: Resultsmentioning
confidence: 92%
“…11 In the works by Hautefeuille et al [9][10][11] , carbon particles were applied to the surface or incorporated in the silicone elastomer to absorb the laser light and locally heat the elastomer to cause combustion. We found that laser induced combustion of the UV-curable silicone used in our 3D printing process is possible without incorporation of carbon particles using a 250 mW, 405 nm violet diode laser.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, absorbing nanocarbon materials are used in order to allow the subtractive manufacturing process to happen. The ionization process that etches the sample can be achieved with several nanocarbon types and it has been found that different allotropic forms may yield different resolutions and etching processes [ 17 ]. In this work, we report the characterization and progress made with carbon nanopowder (633100, Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Instrumentation Considerationsmentioning
confidence: 99%
“…As mentioned, absorbing nanocarbon materials are used in order to allow the subtractive manufacturing process to happen. The ionization process that etches the sample can be achieved with several nanocarbon types and it has been found that different allotropic forms may yield different resolutions and etching processes [17]. In this work, we report the characterization and progress made with carbon nanopowder (633100, Sigma Aldrich).…”
Section: Sample Preparation For Laser Ablationmentioning
confidence: 99%